Hello,
z=(1/√2-1/√2 i)^6=1/8*(1-i)^6=1/8*(√2∡-45°)^6=1/8*8∡-270°=1∡90°=i
======================================================
Answer:
Y = 3/4 X -2
Step-by-step explanation:
Just apply the equation of a straight line (Y=mX+C), remembering that m represents the gradient of the line. This can be found by dividing the change in the y-axis by the change in the x-axis. Then substitute a set of coordinates with your obtained gradient into Y=mX+C to obtain C, i.e. the y-intercept.
Answer:
2
Step-by-step explanation:
/2= 8
8+6= 14
4+3=7
14/7= 2
c
-
p
I believe
maybe im wrong so you might wanna check with someone else